MicroRNA-378 Promotes Osteogenesis-Angiogenesis Coupling in BMMSCs for Potential Bone Regeneration. (1st March 2018) - Zhang, Bo; Li, Yali; Yu, Yang; Zhao, Jinlong; Ou, Yangzhen; Chao, Yu; Yang, Binhui; Yu, Xiaorui
Abstract : Bone tissue regeneration was closely associated with osteogenesis and angiogenesis. The harmonious regulation of osteogenetic and angiogenic growth factors would enhance bone regeneration, while the imbalance of that would lead to local excessive bone formation or vascular mass due to exogenous delivery. Therefore, microRNA is believed to regulate multiple metabolism progress through endogenous signaling pathways on the gene level. In this work, we identified microRNA 378 as a positive regulator of osteogenesis and angiogenesis simultaneously and also observed an increase of microRNA 378 than control in human bone marrow mesenchymal stem cells (hBMMSCs) after osteoblast induction. Besides, osteogenetic and angiogenic gene expression increased simultaneously after overexpression of microRNA 378. Moreover, alizarin red staining and alkaline phosphatase (ALP) staining enhanced, and secretion of vascular endothelial growth factor (VEGF) increased. In this way, we believed miR378 was an ideal target to osteogenesis-angiogenesis coupling for bone regeneration, which provides a potential tool for the gene therapy of bone regeneration.